Characterization and Functional Analysis of Two Transmembrane C-Type Lectins in Obscure Puffer (Takifugu obscurus) - Huang, Ying; Shi, Yan; Hu, Sufei; Wu, Ting; Zhao, Zhe (Frontiers in Immunology, 2020)
C-type lectins (CTLs) play crucial roles in immune responses as pattern-recognition receptors (PRRs). In this study, we identified two CTLs (named ToCTL1 and ToCTL2) from pufferfish Takifugu obscurus. The open reading frames of ToCTL1 and ToCTL2 are 687 and 1380 bp, respectively. Predicted ToCTL1 and ToCTL2 proteins contain a single transmembrane region and one typical carbohydrate recognition domain (CRD). ToCTL1 and ToCTL2 transcripts were detected in all tested tissues, with high levels in the intestine and kidney; and their expressions were significantly altered upon Vibrio harveyi and Aeromonas hydrophila infection. Recombinant ToCTL1-CRD and ToCTL2-CRD were able to agglutinate the Gram-negative and Gram-positive bacteria in a Ca2+-dependent manner. rToCTL1-CRD and rToCTL2-CRD exhibited apparent binding activities against seven kinds of bacteria and polysaccharides (lipopolysaccharide and peptidoglycan). Moreover, rToCTL1-CRD and rToCTL2-CRD could inhibit the growth of four types of bacteria in vitro. These findings collectively demonstrated that ToCTL1 and ToCTL2 serve as PRRs could be involved in host defense against bacterial infection in obscurus pufferfish.